Legal Empowerment Of Coastal Communities Through A Legal Clinic And Civil Rights Education In Aisandami Village, Teluk Wondama Regency - Alice Ance Bonggoibo; Natalia Rahmadani Papuana Dewi; Jumira Jumira (Abdi Masyarakat, 2026)
This article presents a comprehensive socio-legal analysis of a community legal empowerment program implemented in Kampung Aisandami, Teluk Duairi District, Teluk Wondama Regency, West Papua. Utilizing the Progressive Law paradigm and the Asset-Based Community Development (ABCD) approach, this intervention addresses multifaceted socio-legal crises in marginalized coastal regions: the disenfranchisement of civil rights due to unregistered births, the structural normalization of Domestic Violence (KDRT) within patriarchal customary frameworks, and the rise of juvenile delinquency involving inhalant abuse (Lem Fox). Through clinical legal education methodologies driven by a higher education institution (STIH Manokwari), the program successfully facilitated the issuance of birth certificates, restoring the state's recognition of minors' civil rights. Furthermore, legal socialization of Law No. 23 of 2004 was deployed to dismantle cultural barriers silencing KDRT victims. The intervention also tackled the legal vacuum surrounding inhalant abuse using restorative justice paradigms. Ultimately, this community service proves that decentralized legal clinics act as crucial catalysts in bridging the gap between positive law and public legal awareness, fostering legal certainty, utility, and justice in Indonesia's frontier regions.